Systems Silver Iodide-Sodium Iodide and Silver Iodide-Potassium Iodide - Burley, G. (J Res Natl Bur Stand A Phys Chem, 1960)
The phase relations for the systems AgI-NaI and AgI-KI have been determined for the temperature range from room temperature to 685° C, using differential thermal analysis techniques. The AgI-NaI system has a eutectic at 50 mole percent NaI and 384° C. The AgI-KI system has eutectics at 20.8 and 28.5 mole percent KI and 254° C and 244° C, respectively. A compound of formula KAg(3)I(4) is formed with a congruent melting point of 268° C.